Chain of gold eaudiobook - Clare, Cassandra (The Last Hours, 2020)
INCLUDES "FAIRY TALE OF LONDON" A BONUS SHORT STORY FEATURING WILL AND TESSA #1 New York Times bestseller "A pure distillation of fantasy's enchanting mirror held up to our own truths." — Entertainment Weekly "Richly imagined...rife with action, intrigue, and smoldering romance." — Publishers Weekly From #1 New York Times and USA TODAY bestselling author Cassandra Clare comes the first novel in a brand-new trilogy where evil hides in plain sight and love cuts deeper than any blade. Chain of Gold is a Shadowhunters novel. Cordelia Carstairs is a Shadowhunter, a warrior trained since childhood to battle demons. When her father is accused of a terrible crime, she and her brother travel to London in hopes of preventing the family's ruin. Cordelia's mother wants to marry her off, but Cordelia is determined to be a hero rather than a bride. Soon Cordelia encounters childhood friends James and Lucie Herondale and is drawn into their world of glittering ballrooms, secret assignations, and supernatural salons, where vampires and warlocks mingle with mermaids and magicians. All the while, she must hide her secret love for James, who is sworn to marry someone else. But Cordelia's new life is blown apart when a shocking series of demon attacks devastate London. These monsters are nothing like those Shadowhunters have fought before—these demons walk in daylight, strike down the unwary with incurable poison, and seem impossible to kill. London is immediately quarantined. Trapped in the city, Cordelia and her friends discover that their own connection to a dark legacy has gifted them with incredible powers—and forced a brutal choice that will reveal the true cruel price of being a hero.